A Study on Subfertile Women Suffering from Polycystic Ovarian Syndrome with Hyperprolactinaemia and Hypothyroidism as Associated Factors - Anwary, SA; Chowdhury, S; Fatima, P; Alfazzaman, M; Begum, N; Banu, J (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Objective: This study tried to evaluate association of other factors of subfertility in women suffering from polycystic ovarian syndrome (PCOS). Methods: Fifty subfertile women suffering from PCOS attending infertility unit of the Department of Obstetrics and Gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during July 2010 and June 2011, were evaluated. Results: In out study, Age, BMI and duration of marriage range was 20 38 years, 17.70 33.20 kg/m2 and 1 16 years, respectively. Serum FSH was normal (1.0 10.0 mIU/ml) in all 50 (100%) women. Hyperprolactinaemia (serum prolactin >25 ng/ml) was seen in 60%. Hypothyroidism (serum TSH >4 ìIU/ml) was seen in 74% women. Serum LH (>10 mIU/ml) was raised in 74%. USG finding of lower abdomen was abnormal in 75% cases. Conclusion: This study concludes that hyperprolactinaemia and subclinical hypothyroidism were associated causes of subfertility other than PCOS. DOI: http://dx.doi.org/10.3329/jbcps.v31i3.20980 J Bangladesh Coll Phys Surg 2013; 31: 140-143